Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur Di BEI - Sherly Nurainun Bangun (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to obtain empirical evidence regarding the effect of leverage, profitability and dividend policy on firm value in manufacturing companies listed on the Indonesia Stock Exchange, IDX 2016-2019. In this study using secondary data obtained from the site www.idx.co.id by using 40 company that have been selected using purposive sampling method for 4 years a sample of manufacturing companies listed on the Indonesia Stock Exchange. The data analysis technique was carried out by using descriptive statistics and hypothesis testing using the regression method using SPSS ver 24.0. The results of this study indicate that leverage and dividend policy have no effect on firm value, while profitability shows that it has a positive and significant effect on firm value. The implication of this research is that profitability must be managed properly by the company because it can increase the value of the company which will give a good signal to investors.